Nash equilibrium in a pay-as-bid electricity market Part 2 - best response of a producer. (3rd June 2017) - Aussel, D.; Bendotti, P.; Pištěk, M.
Abstract : We consider a multi-leader-common-follower model of a pay-as-bid electricity market in which the producers provide the regulator with either linear or quadratic bids. We prove that for a given producer only linear bids can maximize his profit. Such linear bids are referred as the 'best response' of the given producer. They are obtained assuming the demand is known and some estimate of the bids of the other producers is available. Nevertheless we also show that whenever no best response exists, the optimal profit can be asymptotically attained by a sequence of quadratic bids converging to the so-called 'limiting best response'. An explicit formula for such a sequence is provided.